Compact coupled graphene and porous polyaryltriazine-derived frameworks as high performance cathodes for lithium-ion batteries - Su, Yuezeng; Liu, Yuxin; Liu, Ping; Wu, Dongqing; Zhuang, Xiaodong; Zhang, Fan; Feng, Xinliang (Angewandte Chemie International Edition, 2015)
It is highly desirable to develop electroactive organic materials and their derivatives as green alternatives of cathodes for sustainable and cost-effective lithium-ion batteries (LIBs) in energy storage fields. Herein, compact two-dimensional coupled graphene and porous polyaryltriazine-derived frameworks with tailormade pore structures are fabricated by using various molecular building blocks under ionothermal conditions. The porous nanosheets display nanoscale thickness, high specific surface area, and strong coupling of electroactive polyaryltriazine-derived frameworks with graphene. All these features make it possible to efficiently depress the dissolution of redox moieties in electrolytes and to boost the electrical conductivity of whole electrode. When employed as a cathode in LIBs, the two-dimensional porous nanosheets exhibit outstanding cycle stability of 395 mAhg-1 at 5 Ag-1 for more than 5100 cycles and excellent rate capability of 135 mAhg-1 at a high current density of 15 Ag-1.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Cathode; Graphene; Lithium; Nanostructures; Nitrogen